Competency-Based Medical Education in Radiology: A Survey of Medical Student Perceptions. Issue 3 (August 2021) - Yang, Joseph; Jomaa, Danny; Islam, Omar; Mussari, Benedetto; Laverty, Corinne; Kwan, Benjamin Yin Ming
Purpose: Implementing competency-based medical education in diagnostic radiology residencies will change the paradigm of learning and assessment for residents. The objective of this study is to evaluate medical student perceptions of competency-based medical education in diagnostic radiology programs and how this may affect their decision to pursue a career in diagnostic radiology. Methods: First-, second-, and third-year medical students at a Canadian university were invited to complete a 14-question survey containing a mix of multiple choice, yes/no, Likert scale, and open-ended questions. This aimed to collect information on students' understanding and perceptions of competency-based medical education and how the transition to competency-based medical education would factor into their decision to enter a career in diagnostic radiology. Results: The survey was distributed to 300 medical students and received 63 responses (21%). Thirty-seven percent of students had an interest in pursuing diagnostic radiology that ranged from interested to committed and 46% reported an understanding of competency-based medical education and its learning approach. The implementation of competency-based medical education in diagnostic radiology programs was reported to be a positive factor by 70% of students and almost all reported that breaking down residency into measurable milestones and required case exposure was beneficial. Conclusions: This study demonstrates that medical students perceive competency-based medical education to be a beneficial change to diagnostic radiology residency programs. The changes accompanying the transition to competency-based medical education were favored by students and factored into their residency decision-making.